(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2017)
The ostracods are crustacean arthropods with a wide geographic distribution; they exist in the planet since 542 Ma (Cambrian Period). This crustacean is abundant with 65,000 fossil species and 13,000 current species. They have adapted to all climatic conditions, from deep sea, fresh and brackish waters, to continental humus. The distribution and morphology of the ostracods depends on several ecological factors, but salinity is their main distribution factor. The Ostracods are preserved very well in the geological column because of their high adaptive capacity to survive and evolve; and are important for the identification of paleoecology and paleoclimate. Ostracods are swimmers or benthic, filterers, desparasitadores, scavengers, detritivores, herbivores and predators. In Ecuador, Ostracods have been identified from the Jurassic (174 Ma) in the Oriente Basin. In conclusion, the Ostracods have survived and evolved in the last 500 Ma, from the Cambrian to the Recent, adapting to all kinds of climate. In Ecuador, they have been identified since the Jurassic and adapted to all climate